Lean production model to increase the level of service in a rubber industry SME (LACCEI, 2024)
Companies in the rubber sector face a high rate of non-delivery of complete and on-time orders, even earlier, which intensified with the pandemic. The need for more resources such as rubber, kaolin, or sulfur, which are essential for the production process, leads to a supply of raw materials with proper inventory and production management. Furthermore, the growth in the number of companies in the plastics and rubber sector since 2015 requires companies to meet customers' expectations so that they do not opt for the competition. The present research proposes a model that applies Lean tools such as Autonomous Maintenance, Standardized Work, Kanban, and Heijunka in a company in the rubber sector to increase the fulfillment of the delivery of complete orders on time. With the implementation of the model in the case study, the availability of the extruders was increased by 16.94%. Similarly, an EPEC of less than three days and an inventory index of raw material on hand of more than six days were achieved, obtaining an increase in the OTIF of 20.51% as a crucial result.